The rights of disabled prisoners in Malaysia / Sorahatul Amizah Aminudin ... [et al.] - Aminudin, Sorahatul Amizah; Rashid, Nurayuni; Ahmad Khairuddin, Nur 'Izzati; Sazahan, Nadia Emira (2014)
This paper was conducted to make a research on the rights of disabled prisoners in Malaysia as compared to the United State of America. In Malaysia there are a few laws that governed the right of disabled person under the Person with Disabilities Act 2008 and the law that governed the prisoners under Prison Act 1995 but there were still unclear rights and no specific Act that been amended so far about the disabled prisoners in Malaysia .This research also be looking at the Federal Constitution and Convention on the Rights of Person with Disabilities to know whether the rights was provided under these laws. When comparing to the United State about the right of disabled prisoners, there are a few laws that been referred first, America with Disabilities Act 1990, second, Rehab Act 1973, and a few selected cases that been analyzed to study how they govern the right of disabled prisoners properly and effectively in their country. Then, under this research, the recommendations also been prepared so that Malaysian laws can be improved and knows what action should be taken to ensure that the disabled prisoners' rights be governed properly and effectively as in the United State.